Distance Learning – concepts and contributions - Bušelić, Marija (Oeconomica Jadertina, 2017)
The present paper aims to review distance learning in the context of present definitions, technologies, opportunities, challenges, concepts and contributions as it is fast becoming an essential part of educational systems in both developed and developing countries. By virtue of new technologies the ways of teaching and acquiring new knowledge aren’t confined by space and time any more. New technologies offer great flexibility in when, where and how to distribute teaching and acquiring knowledge offering flexible learning opportunities to individuals and group learners. Distance learning is one of the most rapidly growing fields of education and its potential impact on all education delivery systems has been greatly accentuated through the development of Internet-based information technologies and in particular the World Wide Web. In order to meet the needs of the changing world future distance learning must be time flexible, lacking geographical barriers, competitive cost/value, and learner centred. The chapter is intended for all educational institutions and their academic personnel.
Keywords: distance learning; education; literacy; flexibility; equity; information technology